2009
DOI: 10.1016/j.euroneuro.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

D1-like receptor activation improves PCP-induced cognitive deficits in animal models: Implications for mechanisms of improved cognitive function in schizophrenia

Abstract: Phencyclidine (PCP) produces cognitive deficits of relevance to schizophrenia in animal models. The aim was to investigate the efficacy of the D 1 -like receptor agonist, SKF-38393, to improve PCP-induced deficits in the novel object recognition (NOR) and operant reversal learning (RL) tasks. Rats received either sub-chronic PCP (2 mg/kg) or vehicle for 7 days, followed by a 7-day washout. Rats were either tested in NOR or the RL tasks. In NOR vehicle rats successfully discriminated between novel and familiar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 77 publications
8
79
1
Order By: Relevance
“…In addition, BL1020, glycine uptake inhibitors and the novel antipsychotic, asenapine also show efficacy to reverse the PCPinduced deficit in this task using a 1 min and 1 hour (for sertindole) ITI. We have recently demonstrated involvement of dopamine D 1 receptors (McLean et al 2009a) while others have shown serotonin 5-HT 1A receptor involvement (Nagai et al 2009) in mechanisms for improvement of PCP-induced deficits in this task. This work combined with recent results from a preliminary study using female Long Evans rats suggests that the sub-chronic PCP treated rats have reduced prefrontal cortical dopamine activation in this task providing considerable support for this as a model of cognition in schizophrenia, as hypofrontality is a key feature of schizophrenia pathology (Hill et al 2004).…”
Section: Novel Object Recognitionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, BL1020, glycine uptake inhibitors and the novel antipsychotic, asenapine also show efficacy to reverse the PCPinduced deficit in this task using a 1 min and 1 hour (for sertindole) ITI. We have recently demonstrated involvement of dopamine D 1 receptors (McLean et al 2009a) while others have shown serotonin 5-HT 1A receptor involvement (Nagai et al 2009) in mechanisms for improvement of PCP-induced deficits in this task. This work combined with recent results from a preliminary study using female Long Evans rats suggests that the sub-chronic PCP treated rats have reduced prefrontal cortical dopamine activation in this task providing considerable support for this as a model of cognition in schizophrenia, as hypofrontality is a key feature of schizophrenia pathology (Hill et al 2004).…”
Section: Novel Object Recognitionmentioning
confidence: 94%
“…We have consistently shown that sub-chronic PCP treatment (2 mg/kg twice daily, i.p., for 7 days followed by 7 days washout period) induces a robust enduring deficit in reversal learning performance, again selective for the reversal phase leaving initial phase performance intact in female hooded-Lister rats (Abdul-Monim et al, 2006;2007;Idris et al 2010;McLean et al, 2009a;2009b). …”
mentioning
confidence: 99%
“…PCP hydrochloride (Sigma, UK) was dissolved in 0.9% saline. This dosage regime has proved to be very successful in our laboratory in producing robust reversal learning (Abdul-Monim et al, 2006;McLean et al, 2009) object recognition (Grayson et al, 2007) and attentional set-shifting deficits (McLean et al, 2008a), and social behaviour deficits (Snigdha and Neill, 2008a;. In these experiments we have used female rats and we have previously shown that the stage of oestrous cycle does not affect reversal learning performance (McLean et al, 2009).…”
Section: Drugsmentioning
confidence: 99%
“…This dosage regime has proved to be very successful in our laboratory in producing robust reversal learning (Abdul-Monim et al, 2006;McLean et al, 2009) object recognition (Grayson et al, 2007) and attentional set-shifting deficits (McLean et al, 2008a), and social behaviour deficits (Snigdha and Neill, 2008a;. In these experiments we have used female rats and we have previously shown that the stage of oestrous cycle does not affect reversal learning performance (McLean et al, 2009). We have also found females to be better at novel object recognition compared with males (Sutcliffe et al, 2007), and we have demonstrated that female rats are more sensitive to our PCP dosage regime in attentional set-shifting (McLean et al, 2007).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation